Chemotherapy Combined With Surgery in a Case With Metanephric Adenoma - Hu, Shaohua; Zhao, Zhenli; Wan, Zhisheng; Bu, Weizhen; Chen, Songqiang; Lu, Yiqun (Frontiers in Pediatrics, 2022)
Background Metanephric adenoma is an extremely rare renal neoplasm, especially in pediatrics. Chemotherapy combined with surgery in metanephric adenoma has not been reported. Methods We describe a case of metanephric adenoma in a child less than 2 years old, which were treated by chemotherapy combined with surgery. Results Nephron sparing surgery was performed after regular chemotherapy, and the pathological result was metanephric adenoma. Conclusion Pediatric metanephric adenoma is extremely rare; the clinical manifestations and imaging examinations lack specificity. Nephron sparing surgery is recommended as the preferred treatment for metanephric adenoma. Long-term follow-up and more in-depth molecular genetic research are still needed to determine the benign or malignant of metanephric adenoma and whether chemotherapy drugs have an effect on it.